From Treatise to Test: Evaluating Traditional Remedies for Anti-Biofilm Potential - Kadam, Snehal; Madhusoodhanan, Vandana; Bandgar, Anuradha; Kaushik, Karishma S. (Frontiers in Pharmacology, 2020)
Traditional plant-based remedies hold vast potential as novel antimicrobial agents, particularly for recalcitrant infection states such as biofilms. To explore their potential, it is important to bring these remedies out of ancient treatises and into present-day scientific evaluation. Using an example of Indian historical medicine (Ayurveda), we present a perspective towards developing ‘ancientbiotics’ against biofilms. Across compendia, we identified three medicinal plant-based formulations namely, Bryophyllum pinnatum, Cynodon dactylon and Ocimum tenuiflorum, reconstituted in sesame oil in accordance with historical practices. We evaluated the effects of these remedies on well-known biofilm-forming pathogens, P. aeruginosa and S. aureus, with biofilm formation and eradication assays, as well as planktonic assays, and analyzed results based on minimum information guidelines. Based on our approach and results, we provide insights into the considerations and challenges in this ‘treatise to test’ phase of the ancientbiotics pipeline. We believe this will be relevant for future studies exploring anti-biofilm approaches at the interface of historical medicine and contemporary science.